Role of community development on marginalized internally displaced persons (IDPs) in Borno state, Northeast Nigeria - Sadat, Shehu; Wan Jaafar, Wan Munira; Rosnon, Mohd Roslan; Mohd Khir, Azlina (Human Resource Management Academic Research Society, 2021)
The paper examines the role of collective effort towards reducing the plight of the marginalized internally displaced persons (IDPs) in Borno state, Northeast Nigeria, with a focus on community development, and the challenges of community development. The lofty goals embedded in community development especially in providing the needs of IDPs who are subjected to all forms of marginalization which the paper examines. Data was obtained from secondary sources, such as related literature, textbooks, periodicals, and official records, and examined using qualitative content analysis tools. The paper found that efforts of community development towards the IDPs are being hindered by ravaging poverty and illiteracy, lack of information, economic challenges, social inclusion as well as some cultural factors in the country. This paper shows that measures such as learning about the community, listening to community members, access to information, developing an action plan, and implementing an action plan as well as evaluating results of actions that can ensure effective community development in the face of marginalized IDPs. The paper, therefore, concludes that rapid community development should be considered crucial to national development. Hence, it is necessary to encourage community initiatives for self-determination and development because the federal and the state government cannot adequately provide enough for community needs.